2021
DOI: 10.1061/(asce)st.1943-541x.0003161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steel Braces on Robustness of Steel Frames against Progressive Collapse

Abstract: External installation of steel braces is one of the effective approaches to increase the lateral load resistance of the steel moment-resisting frames. However, the effects of existence of steel braces on the robustness of steel moment-resisting frames to resist progressive collapse is still not clear as little study has been carried out. To fill this gap, in this paper, six multi-story steel moment-resisting subframes (three bare frames and three braced frames) were fabricated and tested. Test results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Steel structures are the focus of four papers (Kong et al 2021;Qian et al 2021;Song 2022;Kong et al 2022). Kong et al (2021) report their experimental and numerical findings on the progressive collapse behavior of scaled six-column subframe composite floor systems subjected to the removal of a side column.…”
Section: Overview Of the Special Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steel structures are the focus of four papers (Kong et al 2021;Qian et al 2021;Song 2022;Kong et al 2022). Kong et al (2021) report their experimental and numerical findings on the progressive collapse behavior of scaled six-column subframe composite floor systems subjected to the removal of a side column.…”
Section: Overview Of the Special Collectionmentioning
confidence: 99%
“…The connection between beams and columns is found to be the governing factor of the collapse mechanism. Qian et al (2021) fabricated and tested six multistory steel moment-resisting subframes (three bare frames and three braced frames) aiming to shed light on the effects of the existence of steel braces in the progressive collapse of moment-resisting frames. It is found that the braces can indeed increase the load-resisting progressive collapse capacity and this can be attributed to tensile braces mostly.…”
Section: Overview Of the Special Collectionmentioning
confidence: 99%
“…The presence of steel bracing members in structural bays above the missing column could also influence progressive collapse resistance, as demonstrated by recent experimental and numerical studies. This, however, depends on the type of bracing system since X-bracing, for instance, may ensure increased resistance while V-bracing could have a detrimental effect on performance [43]. Concentric diagonal bracing can affect performance in very different ways depending on whether the bracing members are subject to tension or compression following column loss [44].…”
Section: Collapse Resistance Mechanisms Mobilized By Column Removalmentioning
confidence: 99%
“…Recently, the investigation on the contribution of infill walls to structural resistance against progressive collapse has been extended to post-tensioned RC frames (Shan and Li, 2022) and steel frames (Qian et al, 2023). The results indicated that the infill walls significantly improve progressive collapse resistance of the frames at small deformation.…”
Section: Introductionmentioning
confidence: 99%